(untitled) (LACCEI, 2024)
This research project focused on analyzing the perceived quality of service by patients at the Hospital Clínica, using the SERVQUAL model to study the five dimensions of service (reliability, responsibility, safety, empathy, and tangibles). Two questionnaires were developed for scheduled surgery and emergency areas. After conducting the respective study of the perceived quality of service by the hospital’s patients, it was found that, overall, they were dissatisfied. The dimensions that had the greatest influence on the perceived quality of service were reliability, responsibility, and safety, while the tangible elements dimension had the least influence. The study identified opportunities for improvement in each dimension of service, and specific recommendations and suggestions were made to the Hospital Clínica to improve the quality of service provided. Overall, the study highlights the importance of paying attention to patient perceptions and using this information to improve the quality of service in the hospital.